Small bowel obstruction after endoscopic fragmentation of a gastric bezoar: An unexpected complication - Nunes, Gonçalo; Patita, Marta; Barosa, Rita; Canhoto, Manuela; Roque Ramos, Lídia; Lages, Patrícia; Fonseca, Jorge (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Nunes G, Patita M, Barosa R, et al. Small bowel obstruction after endoscopic fragmentation of a gastric bezoar: An unexpected complication. Turk J Gastroenterol 2018; 29: 616-8.